2016
DOI: 10.4103/0972-0707.173188
|View full text |Cite
|
Sign up to set email alerts
|

The bond strength of highly filled flowable composites placed in two different configuration factors

Abstract: Objective:The aim of this study was to evaluate the microtensile bond strength (μTBS) of different flowable composite resins placed in different configuration factors (C-factors) into Class I cavities.Materials and Methods:Fifty freshly extracted human molars were divided into 10 groups. Five different composite resins; a universal flowable composite (AeliteFlo, BISCO), two highly filled flowable composites (GrandioSO Flow, VOCO; GrandioSO Heavy Flow, VOCO), a bulk-fill flowable composite (smart dentin replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
2
7
0
2
Order By: Relevance
“…Higher filler content is therefore not a higher bond strength indicator [35]. On the other hand, the reason for the differences in µTBS results between the incrementally applied nanohybrid RC (Grandio ® SO) and packable bulk fill RC (X-tra fil ® ), despite their similar filler mass fraction (around 85%), may be related to the involvement of the other parameters such as particle size, density, type, and ratio of monomers or photoinitiators in both of them [36], [37] This could also be due to the incremental packing technique used with the nanohybrid RC that providing better polymerization of the RC material [38], [39].…”
Section: Discussionmentioning
confidence: 98%
“…Higher filler content is therefore not a higher bond strength indicator [35]. On the other hand, the reason for the differences in µTBS results between the incrementally applied nanohybrid RC (Grandio ® SO) and packable bulk fill RC (X-tra fil ® ), despite their similar filler mass fraction (around 85%), may be related to the involvement of the other parameters such as particle size, density, type, and ratio of monomers or photoinitiators in both of them [36], [37] This could also be due to the incremental packing technique used with the nanohybrid RC that providing better polymerization of the RC material [38], [39].…”
Section: Discussionmentioning
confidence: 98%
“…2) raises doubts about whether pre-test failures are exclusively caused by polymerization shrinkage. Sagsoz et al (4) observed satisfactory results of μTBS for bulk fill composites; however, studies that evaluate the bond strength without observing the marginal adaptation before and after polymerization may not be reliable. The preparation of the specimens to evaluate the μTBS, as well as the preparation to observe the tooth/ composite interface in scanning electronic microscopy (7), can generate stresses and cracks in the test body.…”
Section: Discussionmentioning
confidence: 99%
“…These materials have been indicated for use in a single layer in deep cavities (4 to 5 mm) and with a high-factor cavity configuration (Factor-C), simplifying the steps in the clinic (1). Some studies have shown that BFCs have presented adequate marginal adaptation (2), low polymerization shrinkage (1) and satisfactory results in bond strength (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, Giovannetti et al performed some cementation protocols with a flowable composite originally proposed for bulk filling posterior restorations [9]. Their study showed that bulk-fill flowable composites produced better results regarding cavity configurations (C-factors) to build up class I or II cavities [10] than conventional composite resins; in deep cavities, bulk-fill flowable composites exhibited satisfactory bond strength with the remaining structure [11].…”
Section: Introductionmentioning
confidence: 99%